1979
DOI: 10.1111/j.1748-1716.1979.tb06449.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry of myocardial apex in endurance‐trained mice of different ages

Abstract: Mitochondrial volume density, surface density of the outer mitochondrial membrane, the mean number and size of mitochondria, and the mean surface density of crista membranes together with the volume densities of myofibrils and sarcoplasmic space were morphometrically analyzed in cardiac muscle of two groups of sedentary control mice aged 3 and 7 months, and in two groups of mice trained either 1 month rather intensely or 4 months moderately. Of the calculated mitochondrial variables only the surface density of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…They were housed in groups of 4–6 in a temperature controlled room and had free access to laboratory chow and water. Cerebellum, frontal cortex, hippocampus, and heart (the apex portion was selected as a source of uniform ventricular myocytes [35]) tissues were obtained following lethal anesthesia (160 mg/kg ketamine; Sigma, St. Louis, MO) and transcardial perfusion with 0.9% ice-cold saline to remove the circulating blood cells (i.e., until the outflow from the right atrium was clear). The experimental protocol was approved by the Institutional Animal Care Committee.…”
Section: Methodsmentioning
confidence: 99%
“…They were housed in groups of 4–6 in a temperature controlled room and had free access to laboratory chow and water. Cerebellum, frontal cortex, hippocampus, and heart (the apex portion was selected as a source of uniform ventricular myocytes [35]) tissues were obtained following lethal anesthesia (160 mg/kg ketamine; Sigma, St. Louis, MO) and transcardial perfusion with 0.9% ice-cold saline to remove the circulating blood cells (i.e., until the outflow from the right atrium was clear). The experimental protocol was approved by the Institutional Animal Care Committee.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on myocardial mitochondria of endurance-trained animals are controver sial. Several studies have failed to show significant effects of endurance training [Bozner and Meessen, 1969;Gollnick et al, 1971;Guski et al, 1980;Kainulainen et al, 1979;Paniagua et al, 1977;Terzung et al, 1973]. In other cases changes in mitochon dria resulting from endurance training are very localized and have been attributed to focal areas of hypoxia [Arcos et al, 1967], It is possible that some ultrastructural degener ative changes in myocardial mitochondria are evident only in the early stages of train ing [Banister et al, 1971], which may be fol lowed by recovery and conditioning to stress with the result that significant changes in mitochondria of endurance-trained animals may be less easily detected [Arcos et al, 1967], Giant mitochondria have been reported in human myocardium [Harmjanz et al, 1971;Kraus and Cain, 1980] and in dogs subjected to brief periods of hypoxia [Ghadially, 1975] or experimental aortic stenosis [Wollenberger and Schulze, 1961], It is still not clear if giant mitochondria are formed by a simple enlargement of preexisting mito chondria, or by a process of fusion of several mitochondria, or by a combination of both processes [Ghadially, 1975], Our present studies indicate that a fusion of adjacent mitochondria occurs in the formation of the giant mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…In 3-month-old rats no degenerative changes were found in heart myocytes in response to physical training or high altitude [Guski, 1980], In addition, Kainulainen et al [1979] showed that at a certain steady-state level of exercise cardiac muscle cells of trained mice did not differ markedly in ultrastructural properties from those of agematched sedentary controls. Of interest is the fact that whereas heavy physical exercise has been shown to cause myopathy in certain skeletal muscles, characterized by fiber necro sis and a stimulation of the lysosomal system in surviving muscle fibers, exhaustive train ing did not stimulate a similar lysosomal response in cardiac muscle even in aged mice [Salminen and Vihko, 1981;Salminen et al, 1982].…”
Section: Discussionmentioning
confidence: 89%